Handbook of Aircraft Carriers - Sturgeon, Madison, author 648231 (Delhi, India : Learning Press : World Technologies, 2012)
An aircraft carrier is a warship designed with a primary mission of deploying and recovering aircraft, acting as a seagoing airbase. Aircraft carriers thus allow a naval force to project air power worldwide without having to depend on local bases for staging aircraft operations. They have evolved from wooden vessels, used to deploy balloons, into nuclear powered warships that carry dozens of fixed and rotary wing aircraft. Several nations which currently possess aircraft carriers are in the process of planning new classes to replace current ones. The world's navies still generally see the aircraft carrier as the main future capital ship, with developments such as the arsenal ship, which have been promoted as an alternative, seen as too limited in terms of flexibility.